2016
DOI: 10.1007/s10803-016-2820-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Injury-Related Emergency Department Visits in the US Among Youth with Autism Spectrum Disorder

Abstract: Several reports suggest children with Autism Spectrum Disorder (ASD) are more likely to be seen for injury-related ED visits; however, no nationally representative study has examined this question. Using data from the 2008 Nationwide Emergency Department Sample, over a quarter of all visits among those with ASD were related to injury. In the multivariate analyses, the odds of an injury-related visit was 54% greater among those with ASD compared to youth with Intellectual Disability (ID), but 48% less compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 36 publications
4
42
0
Order By: Relevance
“…The parents in this study discussed myriad of safety issues they had experienced (Table ). This information is consistent with the literature that safety is a concern for those with autism and their families (Cavalari & Romanczyk, ; Kalb et al, ; Sirin & Tekin‐Iftar, ; Solomon & Lawlor, ). The literature showed that parents receive inconsistent amounts of information about autism in general at the time their child is diagnosed (Carlsson, Miniscalco, Kadesjo, & Laakso, ; Derguy, Michel, M'Bailara, Roux, & Bouvard, ; Hall & Graff, ; O'Reilly, Karim, & Lester, ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The parents in this study discussed myriad of safety issues they had experienced (Table ). This information is consistent with the literature that safety is a concern for those with autism and their families (Cavalari & Romanczyk, ; Kalb et al, ; Sirin & Tekin‐Iftar, ; Solomon & Lawlor, ). The literature showed that parents receive inconsistent amounts of information about autism in general at the time their child is diagnosed (Carlsson, Miniscalco, Kadesjo, & Laakso, ; Derguy, Michel, M'Bailara, Roux, & Bouvard, ; Hall & Graff, ; O'Reilly, Karim, & Lester, ).…”
Section: Discussionsupporting
confidence: 91%
“…Researchers have indicated that autism is associated with various safety issues. Higher rates of injury exist in the autism population (DiGuiseppi et al, ; Jain et al, ; Kalb et al, ). Guan and Li () completed a retrospective study of 1,367 deaths of people with autism.…”
Section: Introductionmentioning
confidence: 99%
“…There were 7,215,166 participants across the 301 included studies, of which 100,245 participants were identified as having ASD. The bulk of the non-autistic participants came from a few very large population-based studies, with one cohort accounting for over six million participants [21]. Additional file 1: Table S1 shows attributes of individual studies including the method of case ascertainment.…”
Section: Resultsmentioning
confidence: 99%
“…Not all studies have reported higher risk of injury associated with ASD, however. Kalb et al (2016), using data from the 2008 Nationwide ED Sample, a national all-payer ED database, reported that the odds of an injury-related ED visit were 48% lower among children aged 3–17 years with ASD without ID compared to a control group without ASD or ID, after accounting for sociodemographic differences (OR 0.52; 95% CI 0.50, 0.54) (Kalb et al 2016). Notably, ED visits in the ASD group were 5 times more likely to result from a self-inflicted injury than ED visits in the control group (OR 5.4; 95% CI 4.2, 6.9).…”
Section: Introductionmentioning
confidence: 99%